Mental-Health Courts: Expanding the Model in an Era of Criminal Justice Reform - Courtney Black (Washington University Journal of Law & Policy, 2020)
Congress passed the First Step Act in December 2018, which highlighted the need for criminal justice reform. Calls for continued reform come from both the state and federal levels. This Note examines the need for further criminal justice reform, specifically the expansion of access to mental-health courts. For mentally ill prisoners, such expansion would include: referral for early-release consideration, assistance of mental-health court team to transition back into the community, and receipt of community treatment services. To establish such statutory reform, states must consider four statutory considerations: funding of treatment services and individual eligibility based on offense, prior mental-health court interaction, and the amount of time served.
Keywords: First Step Act; criminal justice; reform; criminal justice reform; mental health; mental health courts